Upscaling Ultrafast High-Temperature Sintering (UHS) to consolidate large-sized and complex-shaped ceramics. (December 2022) - Zuo, Fei; Wang, Qiang; Yan, Zheng-Qing; Kermani, Milad; Grasso, Salvatore; Nie, Guang-Lin; Jiang, Bei-Bei; He, Fu-Po; Lin, Hua-Tay; Wang, Li-Guo
Abstract: Despite the well-recognized advantages of Ultrafast High-temperature Sintering (UHS) based on the application of a graphite felt/paper heater, the technology, however, remains mostly suitable to consolidate thin-shaped samples. This work proposes a novel UHS configuration based on the graphite powder medium (P-UHS) to obtain much larger and complex-shaped products. As a proof-of-concept, nearly full dense and homogeneous macro-/microstructures bulk alumina ceramics with size of 10×10×25 mm 3 were densified under a heating rate of 770 °C/min. In comparison with the conventional firing (5 °C/min) approach, the combination of ultrafast heating rate and high temperature (≥1772 °C) induced a very high densification rate mostly driven by lattice diffusion. The very rapid sintering cycle also prevented any detectable carbon contamination. Indeed, the proposed P-UHS approach combines together fine tuning of the microstructures and ultralow energy requirements. Graphical abstract: Image, graphical abstract